2004
DOI: 10.2298/hel0441067t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of female genotype on the efficiency of γ-induced parthenogenesis in sunflower, Helianthus annuus L

Abstract: A comparative study was carried out on the parthenogenetic reaction of Helianthus annuus L. lines and hybrids used as initial female material for parthenogenetic induction. It was established that the mean parthenogenetic responsiveness of the hybrids was considerably higher than that of the lines. The mean parthenogenetic responsiveness of the lines used as initial female material (2607 A, 2607 B, 1607 A, 1607 B, 1234 A and 1234 B) was lower than the mean responsiveness of the hybrids (Albena, Viki, Euroflor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Most experiments studying the effects of ionizing radiation on pollen germination and tube growth were performed in breeding programs or classical genetic studies utilizing acute high doses of gamma irradiation on mature pollen of culture plants to induce haploidy by artificial parthenogenesis (Aleza et al, 2009; Blasco, Badenes, & Del Mar Naval, 2016; Bouvier, Zhang, & Lespinasse, 1993; Lecuyer, Zhang, Tellier, & Lespinasse, 1991; Peixe, Campos, Cavaleiro, Barroso, & Pais, 2000; Todorova, Ivanov, Nenova, & Encheva, 2004; Zhang & Lespinasse, 1991). Since Blakeslee et al, (1922) first reported that pollination with irradiated pollen induces in situ haploid plants of Jimson Weed, this has become a widely used technique which has been applied to produce parthenogenetic seeds of several crop plants, such as apple (Zhang & Lespinasse, 1991), citrus (Aleza et al, 2009), kiwifruit (Pandey, Przywara, & Sanders, 1999), loquat (Blasco et al, 2016), muskmelon (Cuny, Grotte, Dumas de Vaulx, & Rieu, 1993), pear (Bouvier et al, 1993), rose (Meynet, Barrade, Duclos, & Siadous, 1994), winter squash (Kurtar, 2009; Kurtar & Balkaya, 2010), pumpkin (Kurtar, 2009; Kurtar, Balkaya, Ozbakir, & Ofluoglu, 2009), sun flower (Todorova et al, 2004), sweet cherry (Höfer & Grafe, 2003), walnut (Sadat Hosseini Grouh, Vahdati, Lotfi, Hassani, & Biranvand, 2011) and watermelon (Sari, Abak, Pitrat, Rode, & Dumas de Vaulx, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments studying the effects of ionizing radiation on pollen germination and tube growth were performed in breeding programs or classical genetic studies utilizing acute high doses of gamma irradiation on mature pollen of culture plants to induce haploidy by artificial parthenogenesis (Aleza et al, 2009; Blasco, Badenes, & Del Mar Naval, 2016; Bouvier, Zhang, & Lespinasse, 1993; Lecuyer, Zhang, Tellier, & Lespinasse, 1991; Peixe, Campos, Cavaleiro, Barroso, & Pais, 2000; Todorova, Ivanov, Nenova, & Encheva, 2004; Zhang & Lespinasse, 1991). Since Blakeslee et al, (1922) first reported that pollination with irradiated pollen induces in situ haploid plants of Jimson Weed, this has become a widely used technique which has been applied to produce parthenogenetic seeds of several crop plants, such as apple (Zhang & Lespinasse, 1991), citrus (Aleza et al, 2009), kiwifruit (Pandey, Przywara, & Sanders, 1999), loquat (Blasco et al, 2016), muskmelon (Cuny, Grotte, Dumas de Vaulx, & Rieu, 1993), pear (Bouvier et al, 1993), rose (Meynet, Barrade, Duclos, & Siadous, 1994), winter squash (Kurtar, 2009; Kurtar & Balkaya, 2010), pumpkin (Kurtar, 2009; Kurtar, Balkaya, Ozbakir, & Ofluoglu, 2009), sun flower (Todorova et al, 2004), sweet cherry (Höfer & Grafe, 2003), walnut (Sadat Hosseini Grouh, Vahdati, Lotfi, Hassani, & Biranvand, 2011) and watermelon (Sari, Abak, Pitrat, Rode, & Dumas de Vaulx, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Genetically inactive but germinable pollen can be used to stimulate the division of the egg cell, and thus induce parthenogenesis or development of parthenocarpic fruit, including gynogenic haploid production; overcoming minor cross-incompatibilities, and for physiological studies of incompatibility (Stairs and Mergen 1964;Savaskan and Toker 1991;Todorova et al 2004), gene transformation (Pandey 1978) and nucleus substitution (Raquin et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the double haploid lines obtained through this method are determined by the genetic potential of the initial material they were derived from. In spite of the unquestionable benefits from the use of biotechnology methods for acceleration of the breeding process, there are many cases in which they are influenced by the genotypic responsiveness of the investigated plant material (Sauton, 1989;Bouvier et al, 1993;Faris et al, 1999;Todorova et al, 2004;Taşkın et al, 2013;Drumeva and Yankov, 2015). Therefore, additional investigations and certain modifications of the standard methodologies are necessary depending on the specific requirements of the genotype.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis on the parthenogenetic responsiveness of the investigated hybrids revealed significant differences in their reaction (Table 1). A number of authors point out that the genotype of the initial parental forms is an important factor for the successful induction of parthenogenetic development with the aid of irradiated pollen (Sauton, 1989;Bouvier et al,1993;Faris et al, 1999;Todorova et al, 2004;Drumeva and Yankov, 2015). By the present study the effect of the female genotype was observed, expressed in a different response of the investigated hybrids to initiation of parthenogenetic development.…”
mentioning
confidence: 99%